Juvenile development of Callinectes ornatus Ordway, 1863 (Crustacea : Decapoda : Portunidae), from megalopae obtained in the neuston - Bolla Junior, Eduardo Antonio [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP]; Fransozo, Adilson [UNESP] (Magnolia Press, 2008)
The juvenile development of Callinectes ornatus was studied from megalopae collected in the neuston off Ubatuba, São Paulo State, Brazil. The animals were raised in the laboratory under constant temperature (25 +/- 1 degrees C), filtered sea water (35 parts per thousand) from the sampling location, and the natural photoperiod. Eleven stages of the juvenile phase were obtained. The main features of the first juvenile stage diagnostic of the species are: the number of segments in the antenna; number of setae on the exopod, endopod, basal endite and coxal endite of the maxilla, on the exopod, endopod, basal endite, coxal endite and epipod of the 1(st) maxilliped, and on the exopod, endopod and epipod of the 2(nd) maxilliped. Sexual dimorphism becomes apparent from the fourth juvenile stage onwards.
Keywords: Portunidae; Callinectes; swimming crab; juvenile stages; morphological characters; sexual dimorphism